Hubungan antara Pengalaman sebagai Korban Cyberbullying dengan Kepercayaan Diri pada Mahasiswa Program Studi Bimbingan dan Konseling - Ester Julianti Tio Marito Sitorus; Prias Hayu Purbaning Tyas (Lembag, 2024)
This research uses correlative quatitaive research. The sample in this study amounted to 65 students of the Guidance and Counseling Study Program. The data collection technique used in this research is by distributing questionnaires using a google form link with a Likert scale statemen. Data collection uses a cyberbullying experience scale with 34 valid items with a reliability test value of 0.952 and a self-confidence scale with 40 valid items with a reliability test value of 0.970.The results in this study prove: 1) There is a negative relationship with a Pearson Correlation correlation value of -648 with a significance level of 0.000. 2) The level of cyberbullying experience in Guidance and Counseling Study Program students is classified in the high category with a percentage of 38%. 3) The level of self-confidence in students of the Guidance and Counseling Study Program shows 2 levels of categories, namely the low category with a percentage of 32% and the high category with a percentage of 31%.